CARBON QUANTUM DOTS FOR WASTEWATER TREATMENT: PRESENT PROGRESS AND FUTURE PROSPECTS (FUDMA JOURNAL OF SCIENCES, 2024)
Wastewater has continued to pose environmental pollution as various industrial and domestic processes effluents are released daily. As man’s activities increase daily, the possibility of facing water scarcity is imminent, coupled with the climate impacts of wastewater on aquatic lives, soil microorganisms, and agricultural produce. Therefore, several innovative developments have considered using carbon-based nanomaterials like carbon quantum dots (CQDs) to treat and recycle wastewater before they are discharged. These CQDs, just like activated carbon, possess adsorptive abilities that can remove heavy metals, solid pollutants, and foul odors from wastewater. However, they are more unique and effective than the traditional adsorbents because they display quantum effects, fluorescence, high stability, tough compatibility, water solubility, little toxicity, easy to produce, and affordable. This review discusses the nature of CQDs, their chemistries, adsorption abilities, limitations, and recommendations for future application and innovation for economical uses.
Keywords: Carbon Quantum Dots; Adsorption; Fluorescence; Wastewater; Nanomaterials